"Family Is Who They Say They Are"a: Examining the Effects of Cancer on the Romantic Partners of Adolescents and Young Adults. (August 2018) - Moules, Nancy J.; Laing, Catherine M.; Estefan, Andrew; Schulte, Fiona; Guilcher, Gregory M. T.
In this article, we discuss a study we conducted to examine the effects of cancer on romantic partners (i.e., boyfriends and girlfriends, social/romantic/intimate partners) of adolescents and young adults experiencing, or who have experienced, cancer. In this hermeneutic study, we interviewed partners who were involved with an adolescent/young adult with cancer, a cancer survivor who was in a relationship during his treatment, and two healthcare professionals who have worked with these couples and witnessed many other situations of impact, effect, and repercussion. Out of this study, we suggest that partners are affected in many ways that can vary from estrangement, to termination of the relationship, to premature decisions about remaining in the relationship, to family disregard of the partner, and to disregard of the family due to influence of, or relationship with, the partner. We discuss these findings within the context of the larger picture of the psychosocial relational impact of cancer on members beyond those in the immediate and biological family.